Periparturient lipolysis and oxylipid biosynthesis in bovine adipose tissues - Contreras, G. Andres (PLoS One, 2017)
The periparturient period of dairy cows is characterized by intense lipolysis in adipose tissues (AT), which induces the release of free fatty acids (FFA) into circulation. Among FFA, polyunsaturated fatty acids are susceptible to oxidation and can modulate inflammatory responses during lipolysis within AT. Linoleic and arachidonic acid oxidized products (oxylipids) such as hydroxy-octadecadienoic acids (HODE) and hydroxy-eicosatetraenoic acids (HETE), were recently identified as products of lipolysis that could modulate AT inflammation during lipolysis. However, the effect of lipolysis intensity during the transition from gestation to lactation on fatty acid substrate availability and subsequent AT oxylipid biosynthesis is currently unknown. We hypothesized that in periparturient dairy cows, alterations in AT and plasma fatty acids and oxylipid profiles coincide with changes in lipolysis intensity and stage of lactation. Blood and subcutaneous AT samples were collected from periparturient cows at -27±7 (G1) and -10±5 (G2) d prepartum and at 8±3 d postpartum (PP). Targeted lipidomic analysis was performed on plasma and AT using HPLC-MS/MS. We report that FFA concentrations increased as parturition approached and were highest at PP. Cows exhibiting high lipolysis rate at PP (FFA>1.0 mEq/L) had higher body condition scores at G1 compared to cows with low lipolysis rate (FFA<1.0 mEq/L). Concentrations of plasma linoleic and arachidonic acids were increased at PP. In AT, 13-HODE, and 5-, 11- and 15-HETE were increased at PP compared to G1 and G2. Concentrations of beta hydroxybutyrate were positively correlated with those of 13-HODE and 15-HETE in AT. Plasma concentrations of 5- and 20-HETE were increased at PP. These data demonstrate that prepartum adiposity predisposes cows to intense lipolysis post-partum and may exacerbate AT inflammation because of increased production of pro-inflammatory oxylipids including 5- and 15-HETE and 13-HODE. These results support a role for certain linoleic and arachidonic acid-derived oxylipids as positive and negative modulators of AT inflammation during periparturient lipolysis.